Using completeness and defaunation indices to understand nature reserve's key attributes in preserving medium- and large-bodied mammals. (January 2020) - Wen, Zhixin; Cai, Tianlong; Feijó, Anderson; Xia, Lin; Cheng, Jilong; Ge, Deyan; Yang, Qisen
Highlights: Novel indices were used to assess the effectiveness of nature reserves (NR) in preserving medium- and large-bodied mammals. Mammalian completeness and defaunation indices were negatively correlated with each other across 33 NRs in Sichuan Province, China. Habitat heterogeneity and temperature were significant correlates of the two indices, which merit consideration during NR designing. Large-bodied protected herbivores need more conservation efforts because they were the most defaunated taxa. Abstract: Medium- and large-bodied mammals (MLM) are of global interest of conservation due to their indispensable role in ecosystem functioning and sensitivity to human activities. Conservationists regard MLMs' species richness as an important indicator of the conservation effectiveness of nature reserves (NR). However, species richness alone is unable to detect how much of the species pool is realized within local communities, nor the different consequences of loss of species having varying importance in ecosystem functioning on the communities. Here, we simultaneously studied the completeness and defaunation indices (both are useful in informing conservation practices) of MLMs in 33 NRs of Sichuan Province, Southwest China. We evaluated the main correlate (area, habitat heterogeneity, energy, water availability, anthropogenic impact) of each index using Pearson's correlations and generalized least squares regressions. The effects of species' body size, trophic guild and protection status on the defaunation index were also assessed. The results revealed a significant negative relationship between the two indices across the studied NRs. The NRs with larger elevation ranges (greater habitat heterogeneity) tended to have a more complete MLM fauna and less defaunated than NRs with smaller elevation ranges, and NRs with higher mean annual temperature were also more defaunated. At the species level, large-bodied protected herbivores were more defaunated than other MLM groups. Based on the findings, we argue that habitat heterogeneity and temperature should be the key considerations during NR designing of Sichuan Province to conserve MLM biodiversity, and large-bodied protected herbivores are the priority taxa in further conservation practices.